Rechargeable Li-Ion Batteries, Nanocomposite Materials and Applications - Sara El Afia; Antonio Cano; Paul Arévalo; Francisco Jurado (Batteries)
Lithium-ion batteries (LIBs) are pivotal in a wide range of applications, including consumer electronics, electric vehicles, and stationary energy storage systems. The broader adoption of LIBs hinges on advancements in their safety, cost-effectiveness, cycle life, energy density, and rate capability. While traditional LIBs already benefit from composite materials in components such as the cathode, anode, and separator, the integration of nanocomposite materials presents significant potential for enhancing these properties. Nanocomposites, including carbon–oxide, polymer–oxide, and silicon-based variants, are engineered to optimize key performance metrics, such as electrical conductivity, structural stability, capacity, and charging/discharging efficiency. Recent research has focused on refining these composites to overcome existing limitations in energy density and cycle life, thus paving the way for the next generation of LIB technologies. Despite these advancements, challenges related to high production costs and scalability remain substantial barriers to the widespread commercial deployment of nanocomposite-enhanced LIBs. Addressing these challenges is essential for realizing the full potential of these advanced materials, thereby driving significant improvements in the performance and practical applications of LIBs across various industries.